Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper takes stock of the progress made in meeting the objectives under Indonesia's Extended Arrangements (1998-2003) program. The paper addresses progress in achieving the programs' core macroeconomic objectives, with an emphasis on how Indonesia's economic recovery compares with those of the other major Asian 'crisis' countries. A major conclusion of the paper is that, while significant progress has been made against many of the key objectives of the arrangements, Indonesia's overall economic performance has lagged behind others in the region.